Evolution in the surgical management of colorectal liver metastases: Propensity score matching analysis (PSM) on the impact of specialized multidisciplinary care across two institutional eras. Issue 1 (7th June 2018) - Krüger, Jaime A.P.; Fonseca, Gilton M.; Makdissi, Fabio F.; Jeismann, Vagner B.; Coelho, Fabrício F.; Herman, Paulo
Abstract : Background and Objectives: Liver metastases are indicators of advanced disease in patients with colorectal cancer. Liver resection offers the best possibility of long‐term survival. Surgical strategies have evolved in complexity in order to offer resection to a greater number of patients, requiring specialized multidisciplinary care. The current paper focused on analyzing outcomes of patients treated after the development of a dedicated cancer center in our institution. Methods: Patients operated on for CLM from our databank were paired through propensity score matching (PSM), and the initial experience of surgery for CLM was compared with the treatment performed after specialized multidisciplinary management. The demographic, oncological, and surgical features were analyzed between groups. Results: Overall, 355 hepatectomies were performed in 336 patients. Patients operated on during the second era of had greater use of preoperative chemotherapy ( P  < 0.001) as well as exposure to more effective oxaliplatin‐based regimens ( P  < 0.001). Surgical management also changed, with minor ( P  = 0.002) and non‐anatomic ( P  = 0.006) resections preferred over major operations. We also noted an increased number of minimally invasive resections ( P  < 0.001). Conclusion: Treatment in a multidisciplinary cancer center led to changes in oncological and surgical management. Perioperative chemotherapy was frequently employed, and surgeons adopted a conservative approach to liver parenchyma.